Visual outcome of central serous retinopathy - Y J, Shanthi Latha; Madhavi, Chevuturu; Kumar, M. Ashok (International Journal of Research in Medical Sciences, 2017)
Background: Central serous chorioretinopathy (CSCR) is a sporadic disorder of the outer blood retinal barrier. Increasing evidence implicates an abnormal choroidal circulation as the cause of CSCR. The study aimed at the visual outcome of central serous retinopathy for a duration of 6 months from the primary attack. Methods: Study conducted at Department of Ophthalmology in Out Patient Department of Mediciti Medical College Hospital, from June 2013 to December 2014. Total 30 patients’ eyes were treated with placebo treatment with antioxidants for a period of 6 months. Results: Highest prevalence of central serous retinopathy was seen in age group of 20-40 years in 26 eyes (85%), males are predominant i.e. out of 30 patients 27 (90%), risk factors of central serous retinopathy like Type A personality are observed in 3. Associated visual abnormalities like micropsia, central scotomas in 20% of patients, fluorescein angiography showed 60% inkblot pattern. After observation for 6 months visual acuity was spontaneously improved within 4-6 months in 70% of patients, recurrences was seen in 6 patients i.e. 20% is observed. Conclusions: Central serous retinopathy is most commonly seen among 20-40 years age group, with male predominance, unilateral in which Spontaneous resolution of central serous retinopathy is seen in 4-6 months so for which aggressive treatment is not necessary.